Perkembangan Tasyri’ Ekonomi Pada Masa Khulafa ‘Urrasyidin - Evan Hamzah Muchtar (STAI Asy-Syukriyyah, 2016)
For every Muslim all what we do in life must be in accordance with the will of God, as the realization of faith in Him. All righteousness of human deeds are basically contained in the Qur'an and Sunnah. The Qur'an contains provisions Personality 'which requires an understanding of business and search. Efforts to find the provisions of Personality 'to exert maximum power of reason is called ijtihad. Khilafat 'Urrasyidin are scholars or sages who take the place of the Prophet as the Caliph. In his tenure, Khulafa 'Urrasyidin do ijtihad to solve the problems that exist in society. This paper will be presented on the development of tasyri 'to generate the provisions of Personality' during the Khilafat 'Urrrasyidin, the government of Abu Bakr as-Siddiq, Umar bin Khattab, Uthman ibn Affan and Ali bin Abi Talib.